Neuropsychiatric and cognitive comorbidities in epilepsy (Research, Society and Development, 2023)
The epileptic crisis is characterized by a momentary episode of signs and symptoms that are caused by abnormal excessive or synchronous neuronal activity in the brain. On the other hand, epileptic syndrome is defined, according to the International League Against Epilepsy (ILAE), by “a group of clinical and neuroimaging characteristics in electroencephalographic (EEG) findings, many times, supported by specific etiologic findings (structural, genetic, metabolic, immunological and infectious)”. Accordingly, epilepsy patients have multiple neuropsychiatric comorbidities, being depressive disorders the most common, a condition that affects the quality of life and is influenced by numerous external factors. The present study aims to conduct a literature review based on the analysis of articles published from 2010 to 2022 in the PubMed (Medline) and Science Direct databases on epilepsy, its cognitive compromising and its neuropsychiatric comorbidities, using the terminology indicated by the System of Descriptors in Health Sciences (DeCS) and a set of predetermined criteria to select the best articles on the subject. Therefore, approaching psychiatric comorbidities, such as depressive disorders and cognitive deficiencies, in epilepsy is essential in light of its high prevalence and the negative repercussions in the patient's life. Consequently, more in-depth studies are necessary to provide a better prognosis for epilepsy patients and to evaluate the side effects and the clinical repercussions of Anti-Epileptic Drugs (AEDs).